Experimental analysis of thermal and hydraulic performance of fiber-reinforced polymer fins in compact heat exchangers - Alshameri, Mohammed Hamood Hezam; Azizuddin, Abd Aziz; Arshad, Azim; Mohammed, Haetham G.; Sadeq, Safwan (Penerbit Universiti Malaysia Pahang, 2025)
At present, the significance of fiber-reinforced polymer (FRP) material in fins-and-tube heat exchangers (HEs) has become critical in the thermal industrial sector. This is due to its advantages, such as lightweight nature, ease of manufacturing, and superior resistance to environmental conditions compared to metal materials. The utilization of FRP fins-and-tube heat exchangers has generated considerable interest among researchers, given their pivotal role in various thermal engineering systems. However, the use of carbon nanotube-reinforced polymers (CNTRP) fins in fin-and-tube heat exchangers has not been thoroughly examined, highlighting the need for a comprehensive study. This research aimed to design and fabricate a compact heat exchanger by integrating (CNTRP) fins with copper tubes to create a fully functional heat exchanger unit. The study also assessed the performance of the CNTRP fins by analyzing various geometric and process parameters and investigating their thermal and hydraulic characteristics. Experiments were conducted to evaluate the influence of parameters, such as the number of fins (no fin, six, eight, twelve fins), tube diameter (6.5, 8, 9.5 ), inlet air flow velocity (2.4, 2.9, 3.2, 3.4, and 3.6 ), and inlet temperature (40, 60, and 80 ) on the thermal-hydraulic performance of the heat exchanger. The major findings showed that (CNTRP) fins have a positive impact on heat transfer enhancement, the greater the number of fins, from no fins to six, eight, and twelve fins, the heat transfer coefficient improved by 6%, 10.77%, and 17%, respectively. Meanwhile, the pressure drop rose by 5.8%, 7.4%, and 9% with the same increase in the number of fins. However, this improvement in heat transfer coefficient is accompanied by a rise in pressure drop. Consequently, it is crucial to identify the trade-off in heat exchanger design whereby the increase in pressure drop penalty is weighed against the improvement in heat transfer efficiency.